Tantangan Dunia Pendidikan Dan Implikasinya Terhadap Perubahan Kebijakan - Yufarika, SDA Defi (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
The complex challenges of the world of education affect education policies in various countries. The era of globalization, where competition is getting tougher and everything is all technology, demands that the world of education produce quality human resources and have good skills. Not only have good skills but also good morals in accordance with the values and norms that apply in Indonesia. The development of the world in the current era of globalization is a challenge or opportunity for the world of education to be able to adapt and respond to increasingly complex problems. Economic pressures in life, people's demands for justice and democracy, as well as the strong cultural values that have been eroded by hedonistic, pragmatic, materialistic, and secularistic currents, are signs of the tendency for education to exist in the current era of globalization. This study uses a research library, which is a research object whose object is searched for with various library information such as books, scientific journals, magazines, newspapers, and documents. This study aims to find out what the challenges are in the world of education and their implications for policy changes. The educational curriculum needs to be adapted to the needs and demands of the times. It should be noted that in curriculum development, technology and digitization in learning can improve access and quality of education. There need to be policies that support the use of technology, including adequate infrastructure and training for teachers. In facing the challenges of the world of education, directed and sustainable policy changes are very important to achieve the goal of education that is inclusive, quality, and relevant to the needs of the times.